Computer-Mediated Communication in Language Learning Vis-A-Vis Proficiency in the English Productive Skills among Students of Selected Higher Education Institutions - Judith M. Maghanoy (JPAIR Institutional Research Journal)
This study aimed to establish any significant relationship between the respondents' use of computer-mediated communication (CMC) in English learning and their proficiency levels in productive skills. This study employed the descriptive-correlational research design involving one hundred ninety eight (198) respondents randomly selected from the population of 917 second year Education and Information Technology students from the four selected higher education institutions in Zamboanga City, Philippines. Researcher-made Survey-Questionnaire in Computer-mediated Communication (CMC) Use in English Learning, the Writing Skill and the Speaking Skill tests were used. Results showed that: 1) respondents were average users of CMC in English learning; 2) they obtained average proficiency level in their productive skills; 3) there was a significant relationship between the respondents' CMC use in English learning and proficiency level in productive skills; 4) there was a significant difference in the respondents' CMC use in English learning when data were grouped according to gender and type of school while no significant difference in course; and 5) there was a significant difference in the respondents' proficiency levels when data were grouped according to course and type of school while no significant difference in gender. It can be deduced that the type school is a contributing factor for the respondents' CMC use in English learning and proficiency levels. The school can advocate the use of CMC in the class to create impact and produce meaningful teaching-learning environment to students.